FAKTOR-FAKTOR YANG MEMPENGARUHI TINGGINYA TINGKAT MINAT MAHASISWA TERHADAP JURUSAN MANAJEMEN PENDIDIKAN DI UIN ALAUDDIN MAKASSAR - Djafar, Hamsiah (Inspiratif Pendidikan, 2017)
Educational Development is a process of administrative subsystem structural reforms relating to the educational management and operational subsystem relating to the management of education and implementation of teaching learning activities at any educational institution in order to achieve the level of participation, efficiency, effectiveness and relevance of higher education. This research was a field research in form of a descriptive study. The data collection used was observation, interviews, and documents. Data analysis techniques used were editing, classifying, verifying, analyzing, and concluding.